Football in times of covid-19: a recapitulation of preventive measures and infection control policies aiming at a safe game environment - Chamari, K.; Dergaa, I.; Mujika, I.; Schumacher, Y. O.; Tabben, M.; Saad, H. B. (International Journal of Sports Physiology and Performance, 2022)
Coronavirus disease 2019 (COVID-19) resulted in sporting event suspensions and cancellations, affecting competition calendars worldwide during 2020 and 2021. This challenged high-performance athletes` capacity to complete physical, technical, or tactical training during restricted movement measures (lockdown). With the Football World Cup organized in the last quarter of 2022, the past period of training and match disturbances challenged footballers concerning their performance and potential higher risk of injury at official matches` resumption. There has been considerable debate about the management of resuming professional football (soccer) during the COVID-19 pandemic. Governing bodies worldwide implemented measures to ensure a safe resumption of football. These precautionary measures aimed to protect the health of players, their support staff, and officials around the pitch and ensure the enjoyment of the event by spectators in the football stadiums. We have therefore narratively reviewed scientific papers about how football has resumed on the pitch and in the stands with special focus on the COVID-19 infection control strategies allowing footballers to perform again and supporters to enjoy the game after the 2020 global stop to sport.